Chiral recognition via a stereodynamic vanadium probe using the electronic circular dichroism effect in differential Raman scattering. Issue 40 (11th October 2021) - Machalska, Ewa; Hachlica, Natalia; Zajac, Grzegorz; Carraro, Davide; Baranska, Malgorzata; Licini, Giulia; Bouř, Petr; Zonta, Cristiano; Kaczor, Agnieszka
Abstract : Differential ECD-Raman measurements can be conveniently used to monitor molecular interactions and molecular spectroscopic properties. Abstract : Intermolecular interactions sensitive to chirality occur in many biological events. We report a complex formation between a versatile vanadium-based probe and a chiral co-ligand monitored via the combination of electronic circular dichroism (ECD) and Raman scattering. This "ECD-Raman" effect was discovered relatively recently and can be measured using a Raman optical activity (ROA) spectrometer. Simulated spectra based on experimental ECD and degree of circularity (DOC) values agree with the observed ones. Sensitive recognition of the chiral enantiopure co-ligand is thus enabled by a combination of resonance of the excitation light with the diastereoisomeric complex, co-ligand complexation, circular dichroism, and polarized Raman scattering from the achiral solvent. Relatively dilute solutions could be detected (10 −4 mol dm −3 ), about 1000× less than is necessary for conventional ROA detection of the pure co-ligand and comparable to concentrations needed for conventional ECD spectroscopy. The results thus show that differential ECD-Raman measurements can be conveniently used to monitor molecular interactions and molecular spectroscopic properties.